Model Penafsiran Quraish Shihab terhadap Pemaknaan dan Pemahaman Al-Quran dalam Chanel Youtube Najwa Shihab - Mahbub Ghozali; Alfi Ifadatul Umami (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2022)
Abstract: The meaning of the Qur'an made on social media can occur in the form of an oral and more dialectical explanation. Quraish Shihab interprets the Qur'an on Najwa Shihab's Youtube Channel by responding to people's understanding of the Qur'an. This study aims to analyze the cultural structure of understanding and meaning depicted on Najwa Shihab's Youtube Channel. This study uses qualitative methods and content analysis as a data analysis tool. Meanwhile, the achievement of cultural analysis in language uses a structuralist anthropological approach introduced by Levi-Strauss. This study concludes that the explanation of meaning is carried out through two mechanisms; delegitimization as a critique of understanding and figurative as a meaning mechanism that is relevant to the understanding of new issues that exist. The delegitimization and figurative mechanisms used represent the actual cultural structure of meaning in Quraish Shihab and the puritanical and modernist-quasi-objective culture of understanding. The culture that is represented in the structure of meaning on social media shows another function of the representation of the Qur'an on Youtube as a medium of